Novel laser induced fluorescence with hyperspectral imaging of amplifying fluorescent melamine resin for TNT vapor detection. (December 2020) - Elbasuney, Sherif; Baraka, Ahmad; El-Sharkawy, Yasser H.
Highlights: The facile synthesis of porous melamine resin as a novel sensor. Novel ability to capture TNT vapors with visual change in color. Novel fluorescence/quenching phenomenon upon exposure to TNT vapors. Amplified chemosensory response via wired receptors in a series. Novel hyperspectral imaging with 2D moving average filter to develop enhanced color intensity maps. Abstract: Terrorism by means of explosive is an imminent threat; instant detection of explosive vapors is a vital demand. Explosives are electron deficient molecules; the vicinity of explosives to fluorescent material could hinder excitation migration resulting in fluorescence quenching. This study reports on the facile synthesis of porous melamine–formaldehyde–diethylenetriaminepentaacetic acid (MF–DTPA) resin with surface area of 162 m 2 /g, and average pore diameter is 94.7 (Å). MF–DTPA resin demonstrated unique ability to capture TNT vapors with complete change in its color from white to reddish. Furthermore, MF–DTPA resin demonstrated novel fluorescence properties over visible band (400–560 nm) and infrared band (700–760 nm) when stimulated with UVA LED source at 385 nm of 100 mW power. These two emission bands were completely quenched when MF–DTPA was subjected to TNT vapors. Amplified chemosensory response was archived via wired receptors in a series. Hyperspectral imaging associated with 2D moving average filter was employed to develop enhanced color intensity maps.